The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1123/jsep.35.4.387
|View full text |Cite
|
Sign up to set email alerts
|

Who Thrives Under Pressure? Predicting the Performance of Elite Academy Cricketers Using the Cardiovascular Indicators of Challenge and Threat States

Abstract: This study assessed whether cardiovascular (CV) reactivity patterns indexing challenge and threat states predicted batting performance in elite male county (N = 12) and national (N = 30) academy cricketers. Participants completed a batting test under pressure, before which CV reactivity was recorded in response to egothreatening audio instructions. Self-reported self-efficacy, control, achievement goals, and emotions were also assessed. Challenge CV reactivity predicted superior performance in the Batting Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
149
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(156 citation statements)
references
References 46 publications
(84 reference statements)
4
149
2
1
Order By: Relevance
“…These results therefore have important implications for safety and error avoidance in safety critical industries (e.g., aviation, surgery, and driving), and for improved performance in stressful applied environments (e.g., sport and military). While more complex psychophysiological indices of challenge and threat states may reflect subconscious evaluations that are free from reporter bias to be assessed (e.g., Blascovich et al, 2004;Moore et al, 2012;Turner, Jones, Sheffield, & Cross, 2012;Turner, Jones, Sheffield, Slater, Barker, & Bell, 2013), the current study provides further support for the validity of expedient self-report measures that can be easily collected in applied environments.…”
Section: Discussionmentioning
confidence: 65%
“…These results therefore have important implications for safety and error avoidance in safety critical industries (e.g., aviation, surgery, and driving), and for improved performance in stressful applied environments (e.g., sport and military). While more complex psychophysiological indices of challenge and threat states may reflect subconscious evaluations that are free from reporter bias to be assessed (e.g., Blascovich et al, 2004;Moore et al, 2012;Turner, Jones, Sheffield, & Cross, 2012;Turner, Jones, Sheffield, Slater, Barker, & Bell, 2013), the current study provides further support for the validity of expedient self-report measures that can be easily collected in applied environments.…”
Section: Discussionmentioning
confidence: 65%
“…Robotic technology may therefore also have benefits in terms of surgeons' long-term mental and physical health, an important consideration given recent concerns regarding surgeons' elevated suicide risk and reduced life expectancy [30,31]. In Stress in robotic surgery 14 addition, when compared to the 'threat' cardiovascular response, the 'challenge' cardiovascular response has been shown to predict superior motor performance in stressful environments [32].…”
Section: Stress In Robotic Surgery 13mentioning
confidence: 99%
“…Spare resources might be a consequence of lower cognitive workload required to perform surgical tasks on the robotic platform than the laparoscopic platform [5,6]. In the operating room, these extra cognitive resources could be used to more effectively deal with other demands, such as decision-making and communication, or to better cope with the many Stress in robotic surgery 15 noises and distractions that are often encountered [32]. Such issues would be interesting to examine in future research.…”
Section: Stress In Robotic Surgery 13mentioning
confidence: 99%
“…Challenge cognitive appraisals occur when secondary appraisal indicates that an individual's coping potential is sufficient, thus deeming harm less likely. Challenge is considered an adaptive approach associated with superior performance, and threat a maladaptive approach associated with inferior performance in a range of tasks (e.g., Blascovich, Seery, Mugridge, Norris, & Weisbuch, 2004;Moore, Vine, Wilson, & Freeman, 2012;Schneider, 2008;Turner, Jones, Sheffield, & Cross, 2012;Turner, Jones, Sheffield, Slater, Barker, & Bell, 2013).…”
mentioning
confidence: 99%
“…In fact, it is often precisely the importance of an event that provides the motivation to succeed (e.g., Eysenck & Calvo, 1992). Finding strategies to successfully promote challenge reactivity in motivated performance situations without altering the perceived demands is a valuable endeavour, as a growing body of research reports the association between challenge reactivity and superior performance compared to threat reactivity (e.g., Blascovich et al, 2004;Moore et al, 2012;Seery, Weisbuch, Hetenyi, & Blascovich, 2010;Turner et al, 2012;Turner et al, 2013). For example, Turner et al (2012) found that challenge CV reactivity was associated with increased performance from base levels in both a cognitive (Stroop Test) and a motor (Netball shooting) task, whereas threat CV reactivity was associated with decreased performance from base levels in both tasks.…”
mentioning
confidence: 99%